2019
DOI: 10.1111/chd.12758
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of extracorporeal membrane oxygenation support after surgery for adult congenital heart disease in children's hospitals

Abstract: Objective Adult congenital heart disease (ACHD) patients who undergo cardiac surgery are at risk for poor outcomes, including extracorporeal membrane oxygenation support (ECMO) and death. Prior studies have demonstrated risk factors for mortality, but have not fully examined risk factors for ECMO or death without ECMO (DWE). We sought to identify risk factors for ECMO and DWE in adults undergoing congenital heart surgery in tertiary care children's hospitals. Design All adults (≥18 years) undergoing congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Eight studies reported improved survival in patients with private relative to government insurance (28, 77, 88, 89, 106, 123, 128, 129). Eight found no survival difference (55, 65, 81, 92, 130–133), with variable cost, complication, readmission, and LOS results (31, 33, 56, 70, 125, 126, 128, 134), including one with higher renal replacement in privately insured patients (83).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight studies reported improved survival in patients with private relative to government insurance (28, 77, 88, 89, 106, 123, 128, 129). Eight found no survival difference (55, 65, 81, 92, 130–133), with variable cost, complication, readmission, and LOS results (31, 33, 56, 70, 125, 126, 128, 134), including one with higher renal replacement in privately insured patients (83).…”
Section: Resultsmentioning
confidence: 99%
“…Of 17 studies examining insurance status, one from South Korea showed higher ECMO use in patients with NHI versus “medical aid” (164). Of 16 U.S. studies, four found no difference (31, 139, 159, 165), 10 showed greater use in patients with private insurance (vs government insurance) (28, 89, 129, 132, 137, 148, 154, 160, 166) or any insurance (vs uninsured) (167). One obstetric study observed higher ECMO use with government insurance (155), and another showed lower ECMO use in insured patients with COVID-19 (138).…”
Section: Resultsmentioning
confidence: 99%
“…In parallel with survivorship, the complexity of ACHD has increased substantially over the past two decades, and there is an increased need for options of respiratory (venovenous (VV) ECMO) and/or mechanical circulatory support (venoarterial (VA) ECMO) [2]. ACHD patients often have a complex anatomy and may have undergone multiple prior interventions, resulting in limitations to vascular access [3]. Because of its special configuration, venopulmonary artery (VPA) ECMO (Figure 1) appears to be an attractive option in patients with ACHD.…”
Section: Introductionmentioning
confidence: 99%